Caracterización de eventos supuestamente atribuibles a la vacunación e inmunización (ESAVI) en estudiantes de 6 a 11 años inmunizados contra COVID-19 - Stefania Lisbeth Camacho Maza (2023)
Vaccines are an effective measure to prevent diseases that compromise human health; however, like any medication, they have adverse reactions. For this reason, after the appearance of the new COVID-19 vaccine, doubts arise in the population about its possible post-vaccination effects. That is why this research work was proposed, which aimed to characterize the events supposedly attributable to vaccination in students from 6 to 11 years of age immunized against COVID-19 from the Marieta de Veintimilla Educational Unit in Loja. This was a quantitative, descriptive, nonexperimental, and cross-sectional study, in which 107 children from 6 to 11 years of age who were immunized with the COVID-19 vaccine participated. For this, a follow-up survey was applied via telephone from day 0 to day 8 post-vaccination. Regarding the sociodemographic results, the female sex predominated (53.27%) and in terms of personal health history (97.2%) did not present any personal pathological history. In relation to the ESAVIs presented, it was identified that the most frequent local symptom was pain (40.2%); while the most common systemic symptoms were headache and general malaise, each with 2.8%, lasting 24 to 48 hours post inoculation, being managed at home, with analgesics, phytotherapy and rehydration salts. In conclusion, after the application of the COVID-19 vaccine, the reactions presented were mild and can be managed intradomiciliary, since they constitute a normal response of the organism in the presence of the components of the biological administered